PEMILAHAN SAMPAH LAUT (MARINE DEBRIS) DI PANTAI SAPEKEN, KECAMATAN SAPEKEN, KABUPATEN SUMENEP - Rizal Andi Syabana; Edy Purwanto; Muhammad Hidayaturrahman (Bajang Institute, 2023)
The amount of garbage that pollutes the oceans can be reduced by sorting garbage on the beach. Waste sorting is the initial key to waste management activities. With the process of sorting waste on the beach, it will make it easier for waste managers in the next stage and can provide economic value to the surrounding community. Sorting can be done by doing basic sorting, namely separating organic and inorganic waste and separating wet waste and dry waste. Information about the importance of sorting waste and types of waste is something that is not widely known to the community in Sapeken district. It is proven by the large amount of mixed waste (organic and non-organic) in one bag of plasty k in the same plastik. In addition, knowledge about the adverse impacts of litter thrown into the sea will affect the diversity of fish species and the sustainability of coastal ecosystems in the future is also not widely known by residents in Sapeken district. With the above problems, it is necessary to hold counseling activities on how to sort and manage household waste so that it does not pollute the marine ecosystem to the community in Sapeken district. Pagerungan Besar Village is taken as a pilot project for this Community Service (PkM) activity. The implementation method that will be carried out in the activitiesn PkM for the communityof Pagerungan Besar Village is socialization and practice. This socialization is carried out in order to provide knowledge about the importance of sorting marine debris and direct practice of waste sorting. Inthis activity, 50% of participants who do not understand the dangers of marine debris are produced to 100% better understand and understand the dangers of marine debris for the sustainability of coastal and marine ecosystems. There were 75% of participants who participated in the garbage cleaning activity directly on the pagerungan Besar port beach.